(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The analysis of scientific-methodical and special literature (results of monitoring Internet sources) on the problems of physical training of rowers at the stage of basic training shows that the problem of using modern technologies during the educational and training process remains relevant at the moment. The purpose of this work is the analysis of available innovative technologies in rowing, which are used in the training of athletes, and the prospects of their application in practice. The article examines the modern technologies of training kayakers, which are used in the training of future athletes and the problems of training rowers at the stage of basic training, as well as innovations that can be used in training. Having access to technology that can effectively monitor training and rowing competitions on the water is essential to obtain the necessary information and diagnose the effectiveness of the training process. Coaches need a quantification of workload to ensure an athlete’s progress and balance between training and recovery. Innovative devices, such as smart watches Garmin, improve the controllability of the training process, as they allow you to diagnose the initial level of training, make an individual training program, monitor the performance and physiological functions of the athlete during physical activity in real time and analyze data from different segments of training, for example: frequency heart rate, blood oxygen saturation, energy expenditure during training simultaneously with external load data (speed, distance, pace). Also, the advantage is the relatively low price of smart watches compared to other special measuring devices, which makes them a practical and affordable device for holistic recording of training. The use of innovative technologies contributes to the integration of Ukrainian rowers into the European rowing space.